2002
DOI: 10.1260/026361702760120935
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Biologically Active Compounds from Aqueous Solutions on to Commercial Unmodified Activated Carbons. Part III. Theoretical Description of Paracetamol Adsorption Data at Neutral pH

Abstract: A theoretical description of recently published paracetamol adsorption data on a series of non-modified commercial activated carbons is presented. Nineteen of the most widespread adsorption isotherm equations are analysed and the resulting maximum adsorption values compared. The equations proposed by Weber and Vliet, by O'Brien and Myers as well as by Dubinin and Astakhov led to the highest values of the average correlation coefficient describing the fit of the theoretical data to those obtained experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These characteristics enable efficient adsorption of smaller organic compounds, demonstrating that the adsorbent derived from biomass waste exhibits greater selectivity in eliminating ibuprofen. Terzyk et al [24,25] found that modifying the surface with H 2 SO 4 led to higher efficiency in drug removal compared to using HNO 3 and NH 3 . Macías-García et al [26] conducted research to examine the effects of varying concentrations of H 3 PO 4 (30-85%) on the chemical modification and adsorption capacity of AC that was prepared from kenaf.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics enable efficient adsorption of smaller organic compounds, demonstrating that the adsorbent derived from biomass waste exhibits greater selectivity in eliminating ibuprofen. Terzyk et al [24,25] found that modifying the surface with H 2 SO 4 led to higher efficiency in drug removal compared to using HNO 3 and NH 3 . Macías-García et al [26] conducted research to examine the effects of varying concentrations of H 3 PO 4 (30-85%) on the chemical modification and adsorption capacity of AC that was prepared from kenaf.…”
Section: Introductionmentioning
confidence: 99%